Normothermic Ex Situ Liver Perfusion Enhances Mitochondrial Function of DCD Grafts as Evidenced by High-throughput Metabolomics. Issue 7 (July 2021) - Bhat, Mamatha; Linares-Cervantes, Ivan; Pasini, Elisa; Patel, Preya; Goto, Toru; Noguchi, Yuki; Mazilescu, Laura; Urbanellis, Peter; Selzner, Markus; Selzner, Nazia
Abstract : Background: Normothermic ex situ liver perfusion (NEsLP) reduces reperfusion injury of donation after circulatory death (DCD) grafts and optimizes graft function. The goal of our study was to elucidate how NEsLP impacts global metabolism in DCD grafts using high-throughput metabolomics. Methods: Pig livers were preserved by 2 different techniques: static cold storage and NEsLP. Grafts obtained from heart-beating donors were compared with donation after circulatory death (DCD) grafts with either 30 minutes (DCD30) or 60 minutes (DCD60) ischemia time. Liver tissues were collected at the end of preservation period (T0) with either cold storage or NEsLP (n = 5 per group). Grafts were transplanted into recipient pigs and a second liver biopsy was collected 2 hours following liver transplantation (T1). Snap-frozen tissue was processed and analyzed by Sciex 6600 Q-TOF high-resolution mass spectrometer. Data analysis was performed using MetaboAnalyst 4.0 software. Results: Prolonged ischemia resulted in 38 out of 81 metabolites being differentially abundant over time. Mitochondrial metabolism was significantly affected, with disruption in oxidative phosphorylation capacity i .e the Warburg effect ( P = 3.62E-03) and urea cycle ( P = 7.95E-0.4). NEsLP resulted in improved mitochondrial metabolism and glycolysis (4.20E-02) oxidation of branched chain fatty acids ( P = 4.07E-02). Conclusions: This unbiased, high-throughput metabolomics study reveals that mitochondrial function is globally rescued with NEsLP, associated with improvement in DCD graft function. NEsLP is able to rescue DCD grafts, improving their metabolic function to that of livers not exposed to DCD procurement. Abstract : Supplemental Digital Content is available in the text.